2004
DOI: 10.1161/01.cir.0000138746.14425.00
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Levels and the Expansion of Screen-Detected Abdominal Aortic Aneurysms in Men

Abstract: Background-C-reactive protein (CRP) levels have been shown to predict a number of cardiovascular outcomes. CRP levels have also been found to be elevated in patients with abdominal aortic aneurysms (AAAs). The aim of this study was to assess the relation between CRP levels and rates of expansion of small AAAs. Methods and Results-A cohort of men with small aneurysms was identified in a trial of screening with ultrasound scanning. After initial screening, men were rescanned at 6-to 12-month intervals. CRP level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(19 citation statements)
references
References 34 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Complement reactive protein was examined as marker for expansion in 5 studies17, 18, 19, 20, 21 and in 2 as marker for rupture 22, 23. De Haro et al and Wiernicki et al were the only groups to demonstrate significant correlations with expansion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complement reactive protein was examined as marker for expansion in 5 studies17, 18, 19, 20, 21 and in 2 as marker for rupture 22, 23. De Haro et al and Wiernicki et al were the only groups to demonstrate significant correlations with expansion.…”
Section: Resultsmentioning
confidence: 99%
“…In 9 studies, AAA diameter was described as a marker for expansion8, 17, 19, 21, 40, 56, 57, 58, 59 and in 9 as a marker for rupture 34, 37, 60, 61, 62, 63, 64, 65, 66. Overall, the data are reliable because 2570 patients in total were included and 8 studies were appraised with low bias risk, 7 with medium risk, and only 3 with high risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 illustrate some of the marker investigated for the association with small AAA growth. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Of the marker examined, only 2, namely D-dimer and plasmin-antiplasmin complex, have been associated with AAA growth after adjusting for initial AAA diameter in at least 2 distinct studies ( Table 1). [55][56][57] In the largest of these studies, in which 299 patients with small AAAs were included, it was reported that the use of plasma D-dimer plus initial aortic diameter enable the identification of groups of patients with AAA growth as disparate as 0.4 and 2.5 mm/y.…”
Section: Current Research To Identify Circulating Markers Of Aaa Progmentioning
confidence: 99%
“…The reproducibility of ultrasound measurements were assessed with 95% of measurement differences being !3 mm, as previously reported (15). An AAA was considered present when the abdominal aortic diameter was R30 mm (5,16).…”
Section: Measurement Of Abdominal Aortic Diametermentioning
confidence: 78%